PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA: STUDI KASUS PADA PT. PLN (PERSERO) AREA PELAYANAN DAN JARINGAN YOGYAKARTA - Abdullah Salam (Universitas Alma Ata, 2013)
Abstract This study aims to determine wether the organizational culture, leadership affects the performance through motivation. The sample used 80 respondens by using random samling. In this research, there are two independent variables namely organizational culture and leadership, an intervening variable is motivation, and an dependent variable is performance. Tester using the test instrument validity and reability, data analysis tools using path analysis, where as to test the hypothesis performed using t test, F test, and test determination. The results of this study indicate that there is a direct effect of organizational culture on motivation with a beta value 0,627, the direct influence of organizational culture on performance of 0,708, leadership directly influence the motivation of 0,559, there is a direct effect of leadership on performace of 0,565, motivation directly influence performance of 0,771, the organizational culture indirectly effect the performance through motivation contribute at 0,199, the leadership indirectly affect te performance through motivation contribute at 0,130. Key Word: Organizational Culture, Leadership, Motivation, and Performance.